Digital signal processing laboratory - Kumar B Preetham (London Taylor & Francis, 2005)
Consists of a brief section on theory to explain the underlying mathematics and principles, a problem solving section, and a computer laboratory section with programming examples and exercises using MATLAB and Simulink. Applicable chapters include a hard
Keywords: Signal processing-digital techniques